Method Development and Validation for Detection of Procaterol in Human Urine using Gas Chromatography-Tandem Mass Spectrometry - Jain, Shila; Sahu, Puran Lal; Raj, Srashti; Shrivastava, Abhinav; Maurya, Ashok Kumar; Tonk, Rajiv Kumar; Sahu, Kapendra (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: A simple, sensitive and accurate method for the determination of procaterol in human urine was developed and validated using Gas Chromatography coupled to tandem mass spectrometry (GC-MS/MS) as per the requirements of World Anti-Doping Agency (WADA) and ICH guidelines. Methodology: The sample processing includes deconjugation with enzymatic hydrolysis, Solid Phase Extraction (SPE) procedure using XAD2 column and Liquid-liquid Extraction (LLE) followed by the derivatisation using N-methyl trimethylsilysl trifluoroacetamide (MSTFA). Results: The method included a chromatographic run of 17 min and the calibration curve was linear over the concentration range of 5-40 ng/mL with a correlation coefficient (r) of 0.98. The intra- and inter-day assay precision ranged from 0.75 to 0.94% and 1.2 to 1.70%, respectively. The absolute recovery percentage for procaterol was found to be 83%. The recovery was sufficient to reliable identify the procaterol at or below the level prescribed by WADA ie MRPL 20ng/ ml. The LOQ and LOD was found to be 5 and 3 ng/ml respectively. Conclusion: A simple and sensitive GC-MS/MS method for quantitative estimation of Procaterol was developed and validated as per the WADA ISL and ICH guidelines. This developed method could be also used for therapeutic drug monitoring purposes.
Keywords: Procaterol; Validation; ICH Guideline; GC-MS/MS; Doping control; WADA